2007
DOI: 10.1074/jbc.m704151200
|View full text |Cite
|
Sign up to set email alerts
|

The Transforming Acidic Coiled Coil 3 Protein Is Essential for Spindle-dependent Chromosome Alignment and Mitotic Survival

Abstract: Cancer-associated centrosomal transforming acidic coiled coil (TACC) proteins are involved in mitotic spindle function. By employing gene targeting, we have recently described a nonredundant and essential role of TACC3 in regulating cell proliferation. In this study, we used an inducible RNA interference approach to characterize the molecular function of TACC3 and its role in mitotic progression and cell survival. Our data demonstrate that a TACC3 knockdown arrests G 1 checkpoint-compromised HeLa cells prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 59 publications
7
66
1
Order By: Relevance
“…Previous studies have shown that transforming acidic coiledcoil-containing protein 3 (TACC3) is essential for the mitotic spindle assembly and chromosome alignment, but the mechanism remains largely unknown (14)(15)(16)(17)(18). Here we reveal that TACC3-dependent small microtubule aster formation and sorting near the kinetochores contribute to correct microtubulekinetochore connections.…”
mentioning
confidence: 60%
“…Previous studies have shown that transforming acidic coiledcoil-containing protein 3 (TACC3) is essential for the mitotic spindle assembly and chromosome alignment, but the mechanism remains largely unknown (14)(15)(16)(17)(18). Here we reveal that TACC3-dependent small microtubule aster formation and sorting near the kinetochores contribute to correct microtubulekinetochore connections.…”
mentioning
confidence: 60%
“…We compared cellular stress responses of MCF-7 and MCF-7/caspase-3 cells toward treatments that interfere with microtubule assembly, such as the drug PTX and depletion of TACC3 that was achieved via an inducible RNA interference approach (Schneider et al, 2007). Both cell lines were engineered to express control or TACC3-specific shRNAs upon doxycycline (DOX) treatment (Supplementary Material & Methods).…”
Section: Resultsmentioning
confidence: 99%
“…TACC proteins are evolutionarily conserved and regulate centrosome integrity, centrosome-dependent assembly of microtubules and spindle stability during mitosis (Gergely et al, 2003;Cassimeris and Morabito, 2004;Schneider et al, 2007;Yao et al, 2007). Thereby, TACC3 is predominantly expressed during the G 2 /M phase of the cell cycle, where it localizes to the centrosome and spindle apparatus (Piekorz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of TACC3 by RNAi leads to chromosome misalignment and reduced localization of kinetochore proteins in mitosis, suggesting that TACC3 is required for microtubule-kinetochore interaction [26,29]. Meanwhile, clathrin was also found to be required for chromo- The 'clathrin recruits TACC3′ model.…”
Section: Clathrin Regulates Mitotic Chromosome Alignmentmentioning
confidence: 99%